Pengembangan Media Pembelajaran Interaktif Berbasis Aplikasi Ispring Suite 9 Pada Pembelajaran Bahasa Indonesia Kelas IV Sekolah Dasar - Rindy Ayu Angelia; Navatika Vivayosa; Dwi Anatasia; Levi Hutapea (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to determine the validation, practicality, and effectiveness of interactive learning based on the Ispring Suite 9 application in Indonesian language learning in grade III elementary schools. This research is a Research & Development (R&D) study using the Borg and Gall model. The steps in this research are limited to 6 stages, namely: 1) Potential and Problems, 2) Data Collection, 3) Product Design, 4) Design Validation, 5) Design Revision, 6) Product Trial. Validation was carried out by material experts, design experts, expert educational practitioners and field trials. Based on the results of the Interactive Learning Media validation, it can be seen in the assessment table of the three experts obtained successively, namely 91.07%, 93.1% and 88.63%. So that interactive learning media is suitable for testing. Based on the results of the product trial, the value of students before using interactive learning media was 50.2% and became 82.3% after using interactive learning media. The results of students in using the product have a value above the KKM which is 70, so it can be categorized as “Very Good”. So that Interactive Learning Media Based on the Ispring Suite 9 Application is Effectively Used in Class IV SD